Perioperative Exercise Therapy in Bariatric Surgery: Improving Patient Outcomes - Pouwels S (Dove Medical Press, 2020)
Sjaak Pouwels,1 Elijah E Sanches,1 Eylem Cagiltay,2 Rich Severin,3–5 Shane A Philips5,6 1Department of Surgery, Haaglanden Medical Center, The Hague, the Netherlands; 2University of Health Sciences Turkey, Sultan Abdulhamid Han Education and Research Hospital, Department of Endocrinology and Metabolic Diseases, Istanbul, Uskudar, 34668, Turkey; 3Department of Physical Therapy, College of Applied Health Sciences, University of Illinois at Chicago, Chicago, IL, USA; 4Physical Therapy Program, Robbins College of Health and Human Sciences, Baylor University, Waco, TX, USA; 5Graduate Program in Rehabilitation Sciences, College of Applied Health Sciences, University of Illinois at Chicago, Chicago, IL, USA; 6Department of Physical Therapy, Integrative Physiologic Laboratory, College of Applied Health Sciences, University of Illinois at Chicago, Chicago, IL, USACorrespondence: Sjaak PouwelsDepartment of Surgery, Haaglanden Medical Center, P.O. Box 432, 2501 CK, The Hague, the NetherlandsEmail Sjaakpwls@gmail.comAbstract: Nowadays, obesity and related comorbidities like type 2 diabetes, hypertension, dyslipidaemia and obstructive sleep apnoea syndrome are considered one of the medical challenges of the 21st century. Even with the rise of bariatric and metabolic surgery, obesity and metabolic syndrome are reaching endemic proportions. Even in 2020, obesity is still a growing problem. There is increasing evidence that next to bariatric surgery, exercise interventions in the perioperative period could give extra beneficial effects. In this regard, effects on anthropometrics, cardiovascular risk factors and physical fitness. The aim of this review is to summarise effects of preoperative and postoperative exercise, tools for screening and directions for future research and implementations.Keywords: obesity, exercise, bariatric surgery, metabolic surgery, postoperative outcomes